CHARACTERISTICS OF MATERNAL PREGNANCY AND CHILDBIRTH IN PAYANGAN SUB-SUB-DISTRICT, BALI - Anny Eka Pratiwi; Ni Made Hegard Sukmawati (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2023)
Health and nutrition during pregnancy has a close relationship with child development. Poor nutritional status during pregnancy can have an impact on fetal growth restriction (FGR), low birth weight (LBW) and stunting. Efforts to reduce the prevalence of stunting in Indonesia are carried out through the 1000 days of life program. The Faculty of Medicine and Health Sciences (FKIK) of Warmadewa University integrates the first 1000 days program in the field of education through the implementation of community-oriented medical education. This study aims to provide an overview of the characteristics of pregnancy and childbirth obtained by the first 1000 days program in the Payangan Sub-District, Bali Province. This research was a descriptive study using secondary data sourced from the survey of the Community Oriented Medical Education 1000 Days Early Life education program conducted by FKIK Warmadewa University. The research subjects were pregnant women who lived in the Payangan sub-Sub-District, Gianyar Regency, Bali in 2019-2020. The total number of subjects in this study were 110 people. The data collected consisted of data on demographic characteristics, pregnancy, childbirth, and diet. Of 110 Pregnant women in Payangan Sub-District in 2019-2020, 48% showed an average normal body mass index, most (76%) pregnant women in this region had no history of disease and high and very high-risk pregnancy was found in 61% of the subjects. The diet, environment and family APGAR mostly were considered good, namely in 86%, 72%, and 100% respectively. Most deliveries were by cesarean section, i.e., 59% and most did not have delivery complications (85%).